2008
DOI: 10.1002/jmv.21304
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel human papillomavirus type 16 E1 gene variant with potentially reduced oncogenicity

Abstract: The human papillomavirus (HPV) 16 genome has been studied extensively, although no study has focused on the E1 gene that is implicated in viral DNA replication. After analyzing the E1 region of HPV 16 genomes in 429 cervical samples, 11.2% were found to contain a 63 nucleotides duplication in this region. Sequence analysis of the E6 and the E7 regions has shown that all samples containing this duplication were related to E6‐G350 variant of the HPV 16 (Chi square test, P = 0.0012). A comparison of cervical lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
4
20
1
Order By: Relevance
“…For example, there is a relatively common SNP with the E6 ORF (T350G), which is a non-synonymous change resulting in an amino acid variation (L83V). This variation/mutation might be related to higher oncogenic potential [23], [24], [76], [77], or not [33], [78], [79]; in the current study it was not found to be associated with increased risk. It has been suggested that this mutation is associated with CC in a heterogenic form by world region [58].…”
Section: Discussioncontrasting
confidence: 50%
“…For example, there is a relatively common SNP with the E6 ORF (T350G), which is a non-synonymous change resulting in an amino acid variation (L83V). This variation/mutation might be related to higher oncogenic potential [23], [24], [76], [77], or not [33], [78], [79]; in the current study it was not found to be associated with increased risk. It has been suggested that this mutation is associated with CC in a heterogenic form by world region [58].…”
Section: Discussioncontrasting
confidence: 50%
“…Previously we found a 63-nucleotide duplication, at position 1374 within the E1 gene (E1-1374 ∧ 63nt), in about 10% of HPV16 positive cervical samples. This finding indicates that this particular variation is relatively common in the Croatian population [7], and possibly elsewhere. The same variant was also confirmed to be present in neighbouring Slovenia, in about 8% of samples [8].…”
Section: Introductionmentioning
confidence: 62%
“…E1 was found to be more conserved than other regions [21], and the substitutions of G1515A, A1842G (9/21), A2269T (8/21), and G2337A (5/21) were frequently found in E1. E5 variations have been considered unrelated to malignant transformation.…”
Section: Resultsmentioning
confidence: 99%